RESPON TERHADAP PEMBELAJARAN MOBILE BERBASIS KEARIFAN LOKAL DAN KEPARIWISATAAN PADA MAHASISWA PENDIDIKAN BIOLOGI - Anjani, Isya; Sutrisky, Lalu Edo; Ramdani, Ali; Khery, Yusran (Bioscientist : Jurnal Ilmiah Biologi, 2019)
This study aims to determine the response of students to learning mobile technology based on local wisdom and tourism using descriptive methods. The subjects of this study were 37 Biology Education Study Program students in the first semester of Mandalika Education University in the odd semester of the academic year 2019-2020. This research was conducted with a saturated sampling technique. Student response data obtained by a research questionnaire. Data were analyzed using diagram data. The results showed that students' responses to learning based on local wisdom and tourism were very high. On average 88.5% of lecturers use mobile technology as a means of communication and discussion with students, while the lowest is 69.6%, where only a few lecturers make mobile applications for learning needs. And on average only a few use and link mobile technology with local wisdom products and tourism.